Evaluation of Multi-Walled CNT Particulate Reinforced Ti6Al4V Alloy Based Composites Creep Behavior of Materials Under Static Loads - (:unkn) unknown (GAZI UNIV, 2019)
This study examines the effects of additions of 0.5-5 v/v percentage multi-walled carbon nanotubes into the Ti-6Al-4V matrix by mechanical alloying at low rates and investigates the results of the different sintering conditions on the density, microstructure, and Creep behavior. Mechanical properties, microstructural and density of composite materials (Ti64 / CNT) produced by cold isostatic press molding method have been investigated. MWCNTs reinforced metal matrix composite powders were molded by cold isostatic pressing method using polyacrylonitrile (PAN) based binder. The binder decomposition was carried out by heat treatment. After molding, the specimens have been sintered at high temperature in high vacuum (10-2 bar). Metallographic experiments were carried out to examine density and microstructure. Experimental results indicate Ti-6Al-4V particulate can be sintered to up to 98,5% of calculated density. Maximum hardness was obtained 538 HV at 1300 degrees C for 3 hours and creep life inverse. By using SEM and X-ray diffractometer the characteristics of produced composite samples were investigated. Although Ti-6Al-4V alloys are used as biomaterial, this study aimed at using MWCNTs containing Ti-6Al-4V composites at high temperature applications. Because MWCNTs reinforced Ti-6Al-4V composites are cheaper and has lower weight than the other materials used in this kind of applications.
Keywords: Creep; Sintering; Ti-6Al-4V; Multi-Walled Carbon; Nanotube; NANOTUBE-POLYMER COMPOSITES; CARBON NANOTUBES; MECHANICAL-PROPERTIES; PREALLOYED POWDER; MATRIX COMPOSITES; TI-6AL-4V